Herb–herb pharmacokinetic interaction between Glehniae radix and Ophiopogonis radix in rats using superimposed multiple product ion (SMPI) LC-HR-MS/MS. Issue 47 (7th June 2017) - Shi, Xiaowei; Wang, Shuang; Qian, Qi; Zhou, Na; Qi, Pengcheng; Mu, Xiyan; Wang, Qiao
Abstract : The herb–herb pharmacokinetic interaction between Glehniae radix and Ophiopogonis radix in rats was studied using superimposed multiple product ion (SMPI) LC-HR-MS/MS. Abstract : The combination of Glehniae radix (Beishashen, GR) and Ophiopogonis radix (Maidong, OR) has long been widely used as a traditional Chinese medicine (TCM) herb pair for the treatment of respiratory system and digestive system diseases. The pharmacokinetic interaction mechanism of these two herbs is still unclear. The aim of the study is to elucidate the potential herb–herb pharmacokinetic interaction between Glehniae radix and Ophiopogonis radix in rats. Three groups of Sprague-Dawley rats ( n = 6) were given GR (20 g kg −1 ), OR (20 g kg −1 ) and GR–OR (20 + 20 g kg −1 ), respectively. To study the pharmacokinetic characteristics, nine components were determined in plasma with a newly developed superimposed multiple product ion (SMPI) liquid chromatography high resolution tandem mass spectrometry (LC-HR-MS/MS) method. The SMPI LC-HR-MS/MS method displayed high specificity and sensitivity. Co-administration of GR with OR could significantly increase the area under the concentration–time curve (AUC) of the nine analytes compared with the administration of a single herb (GR or OR). There were no obvious changes for the MRT0−∞ of the nine analytes except that the value for psoralen increased. The t 1/2 values of the nine analytes did not display obvious differences between the GR–OR group and single herb (GR or OR) groups. The Cl/F of the nine analytes significantly decreased in the GR–OR group compared with that in the single herb (GR or OR) groups except for that of isopimpinellin. The present study showed that the GR–OR herb pair had an influence on the pharmacokinetic behaviors of the nine compounds, which could increase the bioavailabilities of the nine analytes, indicating that the co-administration of GR with OR can cause significant herb–herb pharmacokinetic interaction in rats. In addition, this study provides pharmacokinetic experimental evidence for the compatibility (Peiwu) study of the GR–OR herb pair.